The influence of temperature on function of mammalian skeletal muscles - Malak, Bartosz (Akademia Wychowania Fizycznego w Poznaniu)
The influence of the thermal environment on physiological processes and body temperature have been widely studied. Skeletal muscles are one of the tissues that are very sensitive to different thermal conditions. The temperature of muscle, especially in limbs, is frequently different than core temperature and fluctuates daily. For example, the resting muscle temperature of humans (core temperature 37°C) may vary from 29.4 to 34°C but may be increased to 40°C in the same muscle during activity [3]. The change in temperature between resting and working muscle has the potential to considerably alter the rate of contractile muscle properties and power outcomes. This review presents the current state of knowledge regarding the effect of temperature on properties of mammalian skeletal muscle contractions, specifically the biomechanical, metabolic, and neuromuscular aspects.
Keywords: skeletal muscle; physiology; contraction; hypothermia; hyperthermia; metabolism